MAKNA KETAHANAN EMOSIONAL PADA LAGU “TERIMAKASIH SUDAH BERTAHAN” GHEA INDRAWARI ANALISIS SEMIOTIKA FEDHINAND DE SAUSSURE - SusyArlima Vensi; Fitria Yuliani (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
This study aims to describe the meaning of emotional resilience in the lyrics of Ghea Indrawari's song "Terima Kasih Sudah Bertahan" and its relevance to the experiences of the younger generation. This study uses a qualitative descriptive approach with Ferdinand de Saussure's semiotic analysis, emphasizing the relationship between signifier and signified, as well as syntagmatic and paradigmatic relationships. The data, consisting of song lyrics, were analyzed using textual techniques. The results show that the lyrics represent emotional resilience through self-awareness, positive and flexible thinking, self-motivation, self-control, and hope and optimism. Syntagmatically, meaning is constructed through a series of sentences that describe personal struggle and strength. Paradigmatically, meaning is strengthened by the choice of diction such as "bertahan," "berju," and "berhenti." This study concludes that the song functions as a symbolic communication medium that conveys messages of motivation and psychological empowerment, and contributes to the study of cultural communication as a means of emotional reflection in modern society. Keywords: Emotional Resilience, Ferdinand de Saussure, Semiotics, Song Lyrics, Symbolic communication